2020
DOI: 10.1088/1361-665x/aba539
|View full text |Cite
|
Sign up to set email alerts
|

Empirical mode decomposition and its variants: a review with applications in structural health monitoring

Abstract: Structural health monitoring (SHM) is one of the most emerging approaches for early damage detection, which leads to improved safety and efficient maintenance of large-scale civil structures. Data-driven vibration-based SHM techniques rely on sophisticated signal processing methods to analyze and interpret the complex measured data collected from the instrumented structures. Empirical mode decomposition (EMD) is one of the robust time-frequency decomposition techniques that has been widely used in SHM. Numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(55 citation statements)
references
References 114 publications
0
55
0
Order By: Relevance
“…Some other useful reviews for SHM purposes can be found in [ 26 ], in the very recent Ref. [ 14 ], and in Chapter 14 and 15 of Ref. [ 27 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other useful reviews for SHM purposes can be found in [ 26 ], in the very recent Ref. [ 14 ], and in Chapter 14 and 15 of Ref. [ 27 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These are the EMD, the HVD, and the VMD. All of them have been successfully applied for fault and damage detection (see e.g., References [ 14 , 15 ]). These three methods are here quantitatively compared.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 To further enhance the original HHT method, some improved HHT methods have been developed. 17,18 To extract the individual frequency components, Feldman 19,20 developed a new signal decomposition method named as Hilbert vibration decomposition (HVD), and the method has been successfully applied in mechanical engineering vibration signal analysis. In addition, some other time-domain-based time-varying system identification techniques have also been developed in literature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hilbert–Huang transform (HHT) has been applied for non‐stationary signal analysis in many engineering fields 15,16 . To further enhance the original HHT method, some improved HHT methods have been developed 17,18 . To extract the individual frequency components, Feldman 19,20 developed a new signal decomposition method named as Hilbert vibration decomposition (HVD), and the method has been successfully applied in mechanical engineering vibration signal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Damage could be either discrete due to an unwanted shock or progressive due to frequent accumulation of instantaneous damage that can lead to sudden catastrophic failure. Existing damage identification techniques involve analysis in time-domain, frequency-domain, as well as in the time-frequency domain [21] along with various artificial intelligence techniques [111].…”
Section: Introductionmentioning
confidence: 99%